Women and stroke patients are more at risk for fall- related injury among older persons - Darjoko, Sulistyowati Tuminah; Djoeworo, Woro Riyadina; Sapardin, Aprildah Nur (Faculty of Medicine, Trisakti University, 2016)
BackgroundIn Indonesia, the prevalence of injury has increased from 7.9% in 2007 to 8.2% in 2013. Among older persons, falls were the main cause of injury. The objective of this study was to determine the major risk factors and the magnitude of the risk for fall-related injury in older persons.MethodsA study of cross-sectional design was conducted on 4,222 respondents aged 60 years and over. Injury was defined as fall-related injury occurring in the previous 12 months that disturbed activity dailyu living (ADL). Data collection was done by: 1) interview about sociodemographics and health (including hearing impairment, non-communicable diseases and injury) using a questionnaire, 2) measurement of blood pressure and anthropometry (body mass index), 3) examination of vision in the right nd left eyes using tumbling E cards and pinhole eye covers. Data were analyzed using the chi square test and multiple logistic regression with 0.05 significance level.Results After controlling for age, occupation, vision disorder, educational level and economic status, older women had a 2.0-fold increased risk for fall-related injury compared to men (aOR=2.30; 95% CI: 1.93-2.73; p=0.000); subjects with a history of stroke had a 2.0-fold increased risk for fall-related injury compared to those without a history of stroke (aOR=2.07; 95% CI: 1.38-3.09; p=0.000). Educational level was a confounding factor.ConclusionWomen and stroke sufferers were at higher risk of fall-related injury among older persons. Prevention of fall-related injury should be done by older persons through periodic control of their health condition.